Eksplorasi Kangkung Lombok: Perluasan Panen dan Peningkatan Produksi Sebagai Strategi Pengembangan Bisnis - Syarifa Fitria; Lara Isma; Widya Mayastuti; Karina Utami; Herie Saksono (ALETHEIA: Jurnal Sosial & Humaniora, Inovasi, Ekonomi, dan Edukasi, 2024)
Lombok's signature water spinach has become legendary and world-famous. As a horticultural commodity with great potential for development, it is certainly interesting to manage as a business activity. Water spinach as a culinary has succeeded in building interactions, traditions, and literacy that relax and educate those who enjoy its taste. The problem is that the harvested area and production of water spinach show dynamic fluctuations and tend to decline, so it has a significant impact on business development. This study aims to explore the dynamics of the harvested area (Ha.) and the increase in production (Ku) of Lombok's signature water spinach. The approach used is qualitative-exploratory with descriptive statistical analysis. Secondary data includes the harvested area and production of water spinach measured in the period 2014-2022 so that the trends that occur can be identified. In the last eight years, there has been an increase in the harvested area and production of Lombok's signature water spinach cumulatively for the Province of NTB. However, there is also evidence of fluctuations in the harvested area and production which tend to decrease even by 100 percent, in Bima City. At least, there are still six (6) regions that tend to increase the harvested area's growth rate and production of water spinach. The water spinach business management requires policy support that could motivate farmers' interest in planting water spinach with superior seeds and obtain certainty of a prosperous future. Therefore, efforts to develop Farmer HR and involve stakeholders in the management, use, administration, procedures, and trade of water spinach, protection of geographical indications, post-harvest management, branding, and marketing accompanied by forming and expanding partnership networks are necessary. The Government (Central) and Regional Governments are expected to synergize and collaborate for water spinach development. Lombok's typical water spinach has opened up opportunities and provided several challenges to optimize it for the benefit of humanity through innovations that improve prosperity.